Impact of deformable image registration on dose accumulation applied electrocardiograph-gated 4DCT in the heart and left ventricular myocardium during esophageal cancer radiotherapy. - Tong, Ying; Yin, Yong; Cheng, Pinjing; Gong, Guanzhong (Radiation Oncology, 2018)
Background: The deformable image registration (DIR) technique has the potential to realize the dose accumulation during radiotherapy. This study will analyze the feasibility of evaluating dose-volume parameters for the heart and left ventricular myocardium (LVM) by applying DIR.Methods: The electrocardiograph-gated four-dimensional CT (ECG-gated 4DCT) data of 21 patients were analyzed retrospectively. The heart and LVM were contoured on 20 phases of 4DCT (0%, 5%,…,95%). The heart and LVM in the minimum volume/dice similarity coefficient (DSC) phase (Volume min/DSC min) were deformed to the maximum volume/DSC phase (Volume max/ DSC max), which used the intensity-based free-form DIR algorithm of MIM software. The dose was deformed according to the deformation vector. The variations in volume, mean dose (Dmean), V20, V30 and V40 for the heart and LVM before and after DIR were compared, and the reference phase was the Volume max/DSC max phase.Results: For the heart, the difference between the pre- and post-registration Volume min and Volume max were reduced from 13.87 to 1.72%; the DSC was increased from 0.899 to 0.950 between the pre- and post-registration DSC min phase relative to the DSC max phase. The post-registration Dmean, V20, V30 and V40 of the heart were statistically significant compared to those in the Volume max/DSC max phase (p < 0.05). For the LVM, the difference between the pre- and post-registration Volume min and Volume max were only reduced from 18.77 to 17.38%; the DSC reached only 0.733 in the post-registration DSC min phase relative to the DSC max phase. The pre- and post-registration volume, Dmean, V20, V30 and V40 of the LVM were all statistically significant compared to those in the Volume max/DSC max phase (p < 0.05).Conclusions: There was no significant relationship between the variation in dose-volume parameters and the variation in the volume and morphology for the heart; however, the inconsistency of the variation in the volume and morphology for the LVM was a major factor that led to uncertainty in the dose-volume evaluation. In addition, the individualized local deformation registration technology should be applied in dose accumulation for the heart and LVM.